Recent advances of short-pulse laser–induced breakdown effect on charge-coupled device detectors. (December 2022) - Li, Yunfei; Kou, Zilong; Wang, Gong; Hou, Yachong; Xie, Xiaofan; Yu, Yu; Wang, Yulei; Lu, Zhiwei
Abstract: Studies on the interaction between laser radiation and photodetectors have attracted wide attention in the field of photoelectric countermeasures and laser protection measures. A charge-coupled device (CCD) forms the core of a photoelectric system, which is vulnerable to laser-induced damage. Therefore, it is crucial to investigate the laser breakdown mechanism of CCD and sensor robustness should be further improved. Nowadays, continuous-wave, millisecond, nanosecond, picosecond, and femtosecond lasers have been reported to irradiate CCDs and obtain a laser-induced damage threshold. Recently, short-pulse lasers, such as nanosecond, picosecond, and femtosecond lasers, have gradually become a research hotspot in developing military equipment and weapon systems owing to their smaller pulse widths and higher peak powers compared to ordinary pulsed lasers. This review describes the recent advances related to the short-pulse laser induced breakdown of CCDs, introduces the basic structure and working principle of a CCD, and analyzes the damage mechanism of different types of lasers on CCDs as well as the internal relationship between laser parameters and damage effect. This paves the way for application in future information warfare.